Cannabidiol and the Remainder of the Plant Extract Modulate the Effects of Δ9-Tetrahydrocannabinol on Fear Memory Reconsolidation - Murkar, Anthony; Kent, Pam; Cayer, Christian; James, Jon; Durst, Tony; Merali, Zul (Frontiers in Behavioral Neuroscience, 2019)
Background: Δ9-Tetrahydrocannabinol (THC, a CB1 receptor agonist) and Cannabidiol (CBD, a non-competitive antagonist of endogenous CB1 and CB2 ligands) are two key components of Cannabis, that may modulate fear-learning. The CB1 receptor is widely distributed in the cortex and limbic regions associated with fear-learning. Humans with posttraumatic disorder (PTSD) have unregulated CB1 receptor density and reduced availability of anandamide, suggesting a role for the endocannabinoid system in PTSD. Pharmacological blockade of memory reconsolidation may represent a viable target for the development of new treatments for PTSD. In this study, we focused on assessing the impact of the key compounds of the marijuana plant both singly and more importantly in concert, on attenuation of learned fear memory. Specifically, we assessed the impact of THC, CBD and/or the remaining plant materials (post-extraction), on reconsolidation of learned fear. Method: Male Sprague-Dawley rats received six 1.0 mA continuous foot shocks (contextual training). 24 h later, rats were re-exposed to the context. Immediately following memory retrieval (recall) rats received oral administration of low dose THC, high dose THC, CBD, CBD + low THC, CBD + high THC (as isolated phytochemicals and, in separate experiments, in combination with plant background material). Rodents were tested for freezing response to context re-exposure at 24 h and 7 d following training. Results: CBD alone, but not THC alone, significantly attenuated fear-memory reconsolidation when administered immediately after recall. The effect persisted for at least 7 d. A combination of CBD and THC also attenuated the fear response. Plant background material also significantly attenuated reconsolidation of learned fear both on its own and in combination with THC and CBD. Finally, THC attenuated reconsolidation of learned fear only when co-administered with CBD or plant background material. Conclusion: CBD may provide a novel treatment strategy for targeting fear-memories. Furthermore, plant background material also significantly attenuated the fear response. Whereas THC alone had no significant effects, its effects were modulated by the addition of other compounds. Future research should investigate other components present in the plant background material (such a terpenes) for their effects alone, or in combination with pure cannabinoids, on fear-learning.